2017
DOI: 10.46492/ijai/2017.2.2.8
|View full text |Cite
|
Sign up to set email alerts
|

Integrated effect of organic manures and inorganic fertilizers on growth, yield and yield attributes of Radish cv. Kalyanpur Safed

Abstract: A field experiment was conducted in the Department of Horticulture, Janta College Bakewar, Etawah (C.S.J.M. University, Kanpur) during 2013-14, to evaluate the integrated effect of various levels of organic manures and inorganic fertilizers on growth, yield and yield attributes of Radish cv. Kalyanpur Safed. 10 treatments were taken up along with control. Plant height, number of leaves, length and width of leaves, leaf area at various growth stages increased with increasing levels of organic manures and inorga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 1 publication
9
7
0
Order By: Relevance
“…Panchgavya boost the creation of new cells, increase plant vigor, and speed up the development of leaves, all of which aid in capturing more solar energy and better utilization of nitrogen for higher growth qualities. Similar results were also found by Kumar et al [11] and (Vimalendran, Wahab [12]. The significant effect of panchagavya was mainly attributed to its nutrient content, higher biological activity and presence of plant growth promoting substances where apical meristem's activity has a major role in determining the growth and development of the plant's above-ground components and elongates the stem, which was confirmed by Hazarika et al [13].…”
Section: Plant Height (Cm)supporting
confidence: 83%
“…Panchgavya boost the creation of new cells, increase plant vigor, and speed up the development of leaves, all of which aid in capturing more solar energy and better utilization of nitrogen for higher growth qualities. Similar results were also found by Kumar et al [11] and (Vimalendran, Wahab [12]. The significant effect of panchagavya was mainly attributed to its nutrient content, higher biological activity and presence of plant growth promoting substances where apical meristem's activity has a major role in determining the growth and development of the plant's above-ground components and elongates the stem, which was confirmed by Hazarika et al [13].…”
Section: Plant Height (Cm)supporting
confidence: 83%
“…Irrigation was provided frequently and all the recommended cultivation practices were followed. [11,3] . It is also due to the cell elongation by the presence of nitrogenous compounds as it is the basic functions of the nitrogen.…”
Section: Methodsmentioning
confidence: 99%
“…The present findings are in conformity with the findings of (Abdulmaliq et al, 2019; Mohit et al, 2019) [1,18] . The data showed that the maximum number of branches produced were seen under T [15] ; Prabhu et al (2010) [21] and Kumar et al (2014) [11] in tomato. [15] ; Prabhu et al (2010) [21] ; and Kumar et al (2014) [11] in tomato.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The maximum average weight of root is observed (130.27g) at T 10 Vermicompost 10 t/ha+ Azotobacter 100% More +PSB 100% More, followed by (98.47) T 2 (RDF 100:80:50 NPK kg/ha) and minimum is observed at T 9 (49.33 g) Vermicompost 10 t/ha+ Azotobacter 100% More +PSB 100% more. [12] .…”
mentioning
confidence: 99%